Absolute Power on Land Rights Binding Agreement (Study of Verdict No. 698K/Pdt/2017 and Number 483/Pdt.G/2013/PN.Bdg) - Rizal Aditya Nugraha (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2019)
In the sale and purchase of land rights transactions, before the parties make a sale as outlined in the form of a Purchase Deed made before the Land Deed Maker Officer, the parties first make an agreement made in the form of an authentic deed made before a notary called with the Sale and Purchase Agreement (PPJB). Binding Agreement of Purchase made by a notary is always followed by a power of attorney called absolute power of attorney. According to the Instruction of the Minister of Home Affairs No. 14 of 1982, the use of absolute power is prohibited from using it for the transfer of land rights. This study aims to analyze the validity of granting absolute power clauses in the Purchase Binding Agreement which is used as the basis for the transfer of land rights and analyzing the application of absolute power in the Land Purchase Binding Agreement for land rights, especially against Decision Number 698K / Pdt / 2017 and Number 483 / Pdt. G / 2013 / PN.Bdg. The research method used is normative juridical research by examining secondary data, supplemented by a legislative approach and a case approach. This type of research is Analytical Descriptive using legal inventory research, legal principles, legal discovery in concreto. Data analysis was performed using the Normative Qualitative analysis method. The results of this study indicate that: (1) The validity of the absolute power which is entered as a clause in the Binding Agreement of Purchase is valid. Purchase Binding Agreement as a preliminary agreement (Pactum De Contrahendo) which gave birth to the granting of absolute power clause is an inseparable unit of the Purchase Binding Agreement so that the granting of an absolute power clause in the Sale and Purchase Agreement is not included in the absolute power of attorney which is prohibited by applicable laws and regulations. (2) a. Decision Case Number 698K / Pdt / 2017, the granting of absolute power which is used as the basis for the transfer of land rights is invalid because the absolute power of attorney is not based on the principal agreement, thus contradicting the Instruction of the Minister of Home Affairs Number 14 of 1982. b. Decision Case Number 483 / Pdt.G / 2013 / PN.Bdg, the granting of absolute power which is used as the basis for the transfer of land rights is legal, because the absolute power of attorney is based on the principal agreement, so it does not conflict with the Minister of Home Affairs Instruction Number 14 of 1982. Keywords: Binding Agreement of Purchase; Absolute Power of Attorney; Instruction of the Minister of Home Affairs No. 14 of 1982.